2016
DOI: 10.18632/oncotarget.12102
|View full text |Cite
|
Sign up to set email alerts
|

Management of advanced gastric cancer: An overview of major findings from meta-analysis

Abstract: This study aims to provide an overview of different treatment for advanced gastric cancer. In the present study, we systematically reviewed the major findings from relevant meta-analyses. A total of 54 relevant papers were searched via the PubMed, Web of Science, and Google scholar databases. They were classified according to the mainstay treatment modalities such as surgery, chemotherapy and others. Primary outcomes including overall survival, response rate, disease-free survival, recurrence-free survival, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
0
25
0
1
Order By: Relevance
“…Regarding the long‐term prognosis of laparoscopic gastrectomy for advanced gastric cancer, we found one multicenter retrospective study, three reviews, and two meta‐analyses (Table ) published after the guidelines. They showed that there were no marked differences in the long‐term prognosis of laparoscopic and open gastrectomy.…”
Section: Consensus Guidelines For Enhanced Recovery After Gastrectomymentioning
confidence: 99%
“…Regarding the long‐term prognosis of laparoscopic gastrectomy for advanced gastric cancer, we found one multicenter retrospective study, three reviews, and two meta‐analyses (Table ) published after the guidelines. They showed that there were no marked differences in the long‐term prognosis of laparoscopic and open gastrectomy.…”
Section: Consensus Guidelines For Enhanced Recovery After Gastrectomymentioning
confidence: 99%
“…The overall 5‐year survival rate is only 20% (Bang, ; Eric Van Cutsem, ). Cisplatin (CDDP)‐based chemotherapy is a widely used chemotherapeutic regimen to treat gastric cancer (Helleday, Petermann, Lundin, Hodgson, & Sharma, ; Qi et al, ). However, some patients are insensitive to CDDP treatment and develop resistance and cause recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic distal gastrectomy had been proved to be safe for advanced GC 2. Even with advanced systematic therapy, the 5-year overall survival of patients with late-stage GC was not >20% 3. Therefore, it is of great significance to investigate the mechanism of GC progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%